Eutrofização em pequenos reservatórios semiáridos: saneamento rural, aspectos limnológicos e sensoriamento remoto - Coelho, Christine Farias (2017)
This investigation addresses two themes of eutrophication in small semiarid reservoirs: the rural sanitation and water quality monitoring. The initial chapter deals with the Green Module Sewage (GMS) as a mitigating measure of the nutrient supply to the reservoirs. This alternative technology considers the reuse of effluents in productive yards. The GMS assessment constructed in Madalena (CE) included test of sanitary quality in the vegetables, sizing proposal, sludge rate produced and estimation of the maintenance time of the system. Vegetables samples showed thermotolerant coliforms values less than 10 UFC,g-1 and absence of Salmonella sp., indicating that products meet the sanitary standards. The proposed design considers water consumption and sewage production in two situations: (R1) with and (R2) without piped water. From these measurements we got the return coefficient (Cr) and the results indicated values of 25% and 3% for R1 and R2 (respectively), which differs from recommended value (of 80%). GSM shows reduced maintenance demand: removal of every five years and three months, in average. The second part of our investigation assessed the chlorophyll-a (Chl-a) dynamics, besides eutrophication level and characterization of Coloured Dissolved Organic Matter (CDOM) in the reservoirs: Marengo (MAR, 15 hm³), Paus Branco (PB, 5,5 hm³) e (São Nicolau, SN, 0,89 hm³), belonging to the Banabuiú river basin, State of Ceará. The water samples were collected between May 2014 and January 2016 and we applied the Trophic State Index (TSI). The CDOM characterization was obtained through the measurements of absorbance (aCDOM 440) and spectral slopes in the UV (S275- 295) and VIS (S350- 500) regions. MAR presented high trophic level during all period studied, reaching up the highest TSI in May 2015, whereas PB and SN showed varying trophic levels. However, all reservoirs presented advanced TSI from September 2015 mainly due to prolonged drought. The results of CDOM ranged between 0,8 m-1 and 12,9 m-1 among the reservoirs, and this different CDOM magnitude may be related to the hydraulic basins sizes. MAR presented higher mean values for spectral slope in UV domain (SUV = 0.03) when compared to the lower results found to PB and SN (SUV = 0.01), suggesting the occurrence of phytoplankton photoinhibition and this fact can be confirmed by low Chl-a concentration in these latter reservoirs. The reservoirs showed a heterogeneous behavior for SVIS indicating shift in the CDOM source. Slope ratio (SUV:SVIS) reinforces the suggestion that MAR can be more influenced by in situ de CDOM production meanwhile PB and SN tended to allochthonous CDOM sources. In the third chapter we applied Landsat-8 and RapidEye imagery data to estimate Chl-a and CDOM. The RapidEye NIR band showed higher sensitivity to estimate Chl-a of MAR (Nash coefficient > 0.6), The Landsat-8 green band presented the best fit for CDOM simulation in the PB and SN reservoirs, with high reliability degree, indicated by Nash = 0.8. Despite the restrictions identified, the satellite products demonstrated potential for monitoring small reservoirs favoring the management of water resources.